3-D parallel implementation of the wave-equation PML algorithm using distributed system - Akaydin, Oyku; Ramadan, Omar (Springer-Verlag Berlin, 2006)
This paper describes an implementation of the three-dimensional (3-D) parallel algorithm for the wave-equation perfectly matched layer (WE-PML) formulations. The parallel approach is based on domain decomposition technique, and uses the Message Passing Interface (MPI) system. To simplify the parallelization strategy, two-dimensional Cartesian topology and derived data types of MPI are used. The performance of the parallel algorithm has been studied using distributed computing method, and performed on a network of PCs interconnected with Ethernet. A speedup factor of 12.9 has been achieved on the 16 PCs system, as compared to one PC case, for a large size problem.
21st International Symposium on Computer and Information Sciences (ISCIS 2006) -- NOV 01-03, 2006 -- Istanbul, TURKEY
Keywords: wave-equation; perfectly matched layer; parallelizing; Message Passing Interface; interprocess communication; process topology